The influence of nature in the design of ‘Kelarai’ woven mat patterns produced by the Malay community in the East Coast of Malaysia - Marzuki, Ibrahim; Mariam, Idris (2021)
The kelarai woven mat patterns is a common woven art form practised by Malays in the East Coast of Malaysia. The kelarai weave is denoted by the simple arrangement of squares to produce patterns on the mat. It is produced to show the beauty in the art of mat weaving. Each mat produced uses the 'kelarai' design, which is inspired by the elements of nature, as highlighted in the Malay philosophy and culture. This study aims to identify the use of kelarai pattern design, which is still largely not understood by some fractions of the public. This study will describe the types of kelarai pattern designs found on woven mats and the philosophy used, to enhance understanding and appreciation of art. This study is important because the art of kelarai mat weaving has been gradually forgotten, and there is uncertainty on the fate of this Malay art heritage. This is because the younger generation has little interest in continuing this traditional art form. This study is a qualitative study that uses field research method. It will descriptively describe the design of the motif and translate the nature elements highlighted in the design. The study's findings show that the Malays are highly skilled in producing kelarai woven mats despite having no formal education. These crafters have a high knowledge and skills in the arts, especially in using the woven arts to glorify the attributes of Allah S.W.T.